Handbook of college and university teaching a global perspective - Groccia, James E.; Alsudairi, Mohammed A. T.; Buskist, William; Sage eBooks (Thousand Oaks, Calif. : SAGE, 2011)
This comprehensive volume presents international perspectives on critical issues impacting teaching and learning in a diverse range of higher education environments.
Specialized.
Description based on print version details on publisher's website; title from home page (viewed on Mar. 12, 2012).
Keywords: College teaching -- Cross-cultural studies; Learning -- Cross-cultural studies; Universities and colleges -- Administration -- Cross-cultural studies; Electronic books